Knowledge, Attitude and Practices (KAP) of Oral Hygiene among School Children - Tayyaba Zia, Alok Dubey, Tania Naveel, Syma Arshad, Mohamed Gamal Elsehrawy, Sajad Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Poor oral health can have a profound effect on the quality of life. Pain, tooth abscess endurance, eating and chewing difficulty, embarrassment over the form of teeth or missing, discolored, or broken teeth can all have a negative impact on people's everyday life and well-being. In the current study majority of respondents practised appropriate oral hygiene habits such as brushing twice a day using a toothbrush and toothpaste for 2 to 3 minutes. Almost 88 percent were aware of the unhealthy gingival condition and the effects of plaque formation. Approximately 53.14 percent were aware of gum illnesses, and 50.14 percent believed that gum diseases might be avoided if proper oral hygiene practices were followed. Nearly half of the youngsters (52.1 percent) said they would only go to the dentist if they were in pain, despite the fact that the majority (79.4 percent) said regular dental checkups were vital. Fear was stated as the primary reason for not attending the dentist (67.28 percent). The study concluded that the most frequent oral hygiene device used for cleaning teeth is a toothbrush with toothpaste; it was discovered that a larger proportion of students cleansed their teeth in the morning. The primary reason for seeing a dentist was for dental discomfort. Further studies related to knowledge, attitude and practice (KAP) of the students about oral health can be encouraged.